2021
DOI: 10.1016/j.bjps.2020.10.073
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 outbreak on plastic surgery: Taken precautions, distribution of surgical procedures and changes in admissions to outpatient clinic

Abstract: The COVID-19 outbreak is a global problem affecting the world in many respects. In the medical field, its impact on surgical branches as well as clinical branches is inevitable. From the plastic surgery perspective, the COVID-19 outbreak affects the number and distribution of surgeries, patient admissions and educational activities. Although these impacts are predictable, it is beneficial to document these data that would contribute to the proper response to a similar crisis in the future. From this standpoint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 2 publications
2
7
0
Order By: Relevance
“…Other studies have found that plastic surgery procedures most impacted by the pandemic were superficial skin lesions and subcutaneous mass procedures [23], which corroborates our findings of high decrease rates in minor surgeries and surgeries of skin, subcutaneous tissue and mucosa (33.16%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Other studies have found that plastic surgery procedures most impacted by the pandemic were superficial skin lesions and subcutaneous mass procedures [23], which corroborates our findings of high decrease rates in minor surgeries and surgeries of skin, subcutaneous tissue and mucosa (33.16%).…”
Section: Discussionsupporting
confidence: 92%
“…There were also important decrease rates among surgeries of the digestive system and abdominal wall (30.16%), which may also reflect recommendations and alternative management of digestive emergency conditions performed during the pandemic. Guidelines support that only lifethreatening gastrointestinal conditions should undergo surgery, and there were recommendations for clinical treatment in conditions such as uncomplicated appendicitis and cholecystitis [17,23], situations in which conservative management appears to be effective and reduce the length of hospital stay [25].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding plastic surgery, guidelines support the deferral of breast reconstruction and revision procedures [22], which might explain the high decrease rates in breast surgery (40.68%). Other studies have found that plastic surgery procedures most impacted by the pandemic were superficial skin lesions and subcutaneous mass procedures [23], which corroborates our findings of high decrease rates in minor surgeries and surgeries of skin, subcutaneous tissue and mucosa (33.16%).…”
Section: Discussionsupporting
confidence: 92%
“…There were also important decrease rates among surgeries of the digestive system and abdominal wall (30.16%), which may also reflect recommendations and alternative management of digestive emergency conditions performed during the pandemic. Guidelines support that only life-threatening gastrointestinal conditions should undergo surgery, and there were recommendations for clinical treatment in conditions such as uncomplicated appendicitis and cholecystitis [17,23], situations in which conservative management appears to be effective and reduce the length of hospital stay [25].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction was for all types of the plastic surgeries except for post-trauma and skin cancer procedures [ 9 ]. The same model was reported from Turkey [ 10 ] for the first two months after the pandemic and Mexico city [ 11 ] for the first 4-month. However, it is unclear if the same results would have been found for a longer period of time after the pandemic.…”
Section: Introductionmentioning
confidence: 97%